PEMBENTUKAN SAHSIAH UNGGUL MELALUI PEMBELAJARAN ILMU HADIS: SUATU ANALISIS TERHADAP MAHASISWA UNIVERSITI SELANGOR - Ab Latif, Liana; Hamka, Masyitah Az Zahra (Selangor Humaniora Review, 2024)
Islamic teachings state that morality is an important asset in the scope of education where it plays an important role in building individuals with noble morals. Optimal education will produce individuals with high moral values and character. Therefore, there are various components of social learning that can influence students' morals and personality. Therefore, this study aims to examine the concept of superior personality formation among Selangor University students. This study also aims to analyze the effectiveness of learning hadith knowledge to influence the formation of superior personalities among Selangor University students. This study also suggests a suitable alternative in the application of hadith knowledge as an important element for the formation of the superior personality of University of Selangor students. This study uses a qualitative research design. The data of this study was obtained through structured interviews with 3 Selangor University students who had taken the subject of hadith science during their studies. Next, the data from the interview will be analyzed through the atlas.ti software 9. It is hoped that this study can give awareness to students to build a superior personality through the study of hadith. In addition, through this study, we can also produce a generation of Muslim students who not only excel in academics but also excel in personal development so that they can bring a good image in the eyes of the Malaysian community.